High-performance composite H-ZSM-5/alumina catalyst for the methanol-to-ethylene conversion. Issue 5 (4th May 2022) - Zhokh, Alexey A.; Trypolskyi, Andrey I.; Gritsenko, Valentina I.; Serebrii, Tamila G.; Strizhak, Peter E.
Abstract: A series of extruded H-ZSM-5/alumina composite catalysts were prepared and characterized using N2 sorption isotherm, transmission electron microscopy, scanning electron microscopy, infrared spectroscopy, X-ray diffraction, NH3 -TPD, and pyridine adsorption. The methanol conversion over the as-prepared catalyst as well as its components was studied at 500 °C. The catalysts with H-ZSM-5/alumina ratio 3/1 and 1/1 (by mass) catalyst exhibited the highest ethylene selectivity (up to 44%) and the ethylene/propylene ratio up to 10/1, whereas zeolite H-ZSM-5 demonstrated the propylene selectivity up to 30% and the ethylene/propylene ratio 1/8. In contrast, the catalyst with the H-ZSM-5/alumina ratio 1/3 demonstrated no activity toward olefins synthesis. The as-prepared H-ZSM-5/alumina catalysts have a long lifetime in the methanol-to-hydrocarbons conversion, which is several times higher compared to pure zeolite H-ZSM-5. The catalyst regeneration results in recovering the initial catalytic activity. The obtained findings reveal that embedding microporous zeolite in the mesoporous alumina matrix facilitates the mass transfer limitations and decreases the number of strong acid sites. These factors govern an essential performance of the as-prepared catalyst in the methanol-to-ethylene reaction.